Enhancing underwater acoustic communication networks with RIS: Precise performance analysis over κ − μ shadowed fading distribution - Moloy Kumar Ghosh; Mostafa Zaman Chowdhury (Results in Engineering)
Underwater acoustic communication (UAC) networks facilitate long-distance reliable information exchange in marine environments, while reconfigurable intelligent surface (RIS) offers significant benefits in underwater communication by mitigating signal degradation and enhancing propagation efficiency. In this study, the performance of an UAC network integrated with RIS is thoroughly investigated, assuming that the UAC links to follow the κ−μ shadowed fading distribution. RIS is specifically employed in this context to enhance signal propagation in underwater environments by mitigating severe attenuation and fading, offering an adaptable framework that significantly improves communication reliability and efficiency. This work provides an in-depth analysis of the effects of key factors including the fading severity, shadowing intensity, path loss, data transmission rate, and average signal-to-noise ratio (SNR), along with different modulation schemes on the communication performance. Furthermore, the potential influence of RIS technology in advancing robust UAC systems is highlighted in this research. Additionally, a comparative analysis of RIS-assisted UAC and UOWC links based on their OP and ABER performance is illustrated. Moreover, a quantitative comparison between our channel modeling approach and the Gamma distribution is depicted in our study. To evaluate these impacts, the novel closed-form expressions of three essential performance metrics: outage probability (OP), average bit error rate (ABER), and average channel capacity (ACC) are derived in terms of Meijer-G function. To offer deeper insights, the asymptotic behaviors of these performance metrics are also demonstrated. This study also evaluates another important performance metric, Energy Efficiency (EE), which is vital for UAC networks with constrained power sources. Finally, all the derived expressions are verified through Monte-Carlo simulations, confirming the accuracy of the findings. Simulation results reveal that integrating RIS into the UAC network improves OP by 99.98% at 35 dB, and an increase of RIS reflecting elements reduces both ABER and EE by 95.04% and 51%, respectively, at 50 dB. Increasing κ and μ also enhances OP by 97.87% and 92.92% at 10 dB, respectively. Lower shadowing intensity reduces ABER by 96.30% at 25 dB, while increased path loss worsens it by 96.86% at 5 dB, and Higher bandwidth improves EE by 35.42% at 60 dB. Furthermore, reducing the data transmission rate improves OP by 96.77% at 30 dB, and adopting coherent M-ary frequency shift keying (CMFSK) modulation achieves an ABER reduction of over 15% at 40 dB. Additionally, the RIS-assisted UAC link achives an approximate 31% reduction in both OP and ABER at 30 dB, and our channel modeling approach exhibits an perfect alignment of almost 100% with the Gamma distribution after 20 dB, enabling a more precise evaluation of system performance in UAC environments.